2010
DOI: 10.1097/01.ogx.0000368150.56502.80
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Relations of Subcutaneous and Visceral Fat to Bone Structure and Strength

Abstract: Information is lacking from prospective studies on the incidence and risk factors for postoperative nerve injury after routine gynecologic surgery. In 2 retrospective studies, the reported risk of nerve injury from major gynecologic oncologic procedures was estimated to be between 1.1% and 1.9%. This prospective cohort study evaluated the overall incidence and time course of pelvic nerve injury in a population of 616 female patients undergoing elective gynecologic surgery for benign and malignant conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
3
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 0 publications
6
70
3
5
Order By: Relevance
“…Recent studies showed a strong relationship between BMD and abdominal fat distribution; however, these results are inconsistent [13,14,32], and how abdominal fat influences bone metabolism is not clear. An effect of abdominal fat distribution on BMD may be caused by the secretions from the abdominal adipocyte and, additionally, obesity-related metabolic diseases also associated with BMD [32].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recent studies showed a strong relationship between BMD and abdominal fat distribution; however, these results are inconsistent [13,14,32], and how abdominal fat influences bone metabolism is not clear. An effect of abdominal fat distribution on BMD may be caused by the secretions from the abdominal adipocyte and, additionally, obesity-related metabolic diseases also associated with BMD [32].…”
Section: Discussionmentioning
confidence: 92%
“…The ethnic difference in the relationship between %TF and BMD may be due to the reciprocal effect of visceral and subcutaneous fat masses on BMD [14]. With the same increment of BF, Chinese people were reported to have more subcutaneous fat accumulated compared with their European counterparts [21], and the positive correlation between subcutaneous fat and BMD was found to be slightly stronger than the negative correlation between visceral fat and BMD [14]. The opposite associations between subcutaneous fat and visceral fat with BMD are mainly due to the different expressions of biochemical factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although we have not evaluated the composition of visceral vs. subcutaneous fat in this study, previous studies have demonstrated that visceral fat has been shown to be distinct from subcutaneous fat in its effect on bone metabolism [29,30]. Indeed, Gilsanz et al [19] found that the visceral fat exerts negative effects on femoral bone mass and strength, while the subcutaneous fat has positive effects. In another study conducted in 461 healthy Korean subjects, the visceral fat area on abdominal computed tomography scan was inversely associated with BMD, whereas the subcutaneous fat area showed no significant association [28].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that both fat mass and lean mass can contribute to an increase in bone mass, thereby reducing the risk of fractures [10,15,16]; others have demonstrated a detrimental effect of fat mass on bone mass after controlling for body weight [12,17,18]. Additionally, when considering total fat mass, subcutaneous fat was beneficial to bone mass, whereas visceral fat was deleterious [19].…”
Section: Introductionmentioning
confidence: 99%